Interpreted Ideals and Relayed Rights: Video Interpreting Services as Objects of Politics - Haualand, Hilde (Disability Studies Quarterly, 2011)
Key Words Video interpreting, video relay services, comparative politics, legislation, accessibility Abstract The different definitions of video interpreting (VI) services in the U.S., Sweden and Norway serve as a foundation for a discussion on how a technology that at first may appear the same, serves widely different goals in different social and political contexts. In the U.S., video interpreting is defined as a telecommunication service to secure functional equivalence for all. In Sweden, the goal is to secure access to telecommunication services for disabled people. In Norway, VI is defined and organized as an extension of the public sign language interpreter service. This article gives insight into how ideology and politics shape the organization of a certain technology or service and impact the very scope and benefit of the technology itself. Further, the paper shows how the emerging VI services are interpreted, in light of the existing politcal ideals in each of the three countries, and how the services gradually also relay a certain set of rights through the way they are organised.